Prosecuting the “criminals” “undesirable” Chinese and court system in the nineteenth-century Philippines - Galang, Jely A. (2019)
Access online through this link: https://journals.upd.edu.ph/index.php/pssr/article/view/8404/7346
Keywords: Chinese -- Philippines; Court system; Crime; Crimes against noncitizens